Composite solid electrolyte and preparation method and application thereof
By constructing the fluorinated layer and siloxane network stepwise, combined with thermally decomposable crosslinking agents and gradient filler design, the problems of insufficient mechanical strength and ionic conductivity of PVDF-HFP based solid electrolytes were solved, achieving stable cycling and long lifespan of high energy density batteries.
Patent Information
- Application Number
- CN202511495667.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-20
AI Technical Summary
Traditional polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) based solid electrolytes are insufficient in mechanical strength, have high filler-matrix interfacial impedance and limited dielectric properties, making it difficult to meet the requirements of high energy density batteries. Existing technologies cannot simultaneously improve ionic conductivity and mechanical properties.
By constructing a fluorinated layer and a siloxane network in steps, and combining them with a thermally decomposable crosslinking agent to form a three-dimensional network structure, and by using a gradient filler design, the interfacial impedance is reduced, and the tensile strength and lithium-ion transference number are improved.
Significantly reduces interface impedance by more than 30%, increases tensile strength to ≥8MPa, ionic conductivity to ≥1×10-3S/cm, lithium-ion transference number to ≥0.6, achieves stable cycling of high energy density batteries, and extends cycle life by 40%.
Smart Images

Figure CN120978176A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid electrolyte materials technology, specifically relating to a composite solid electrolyte, its preparation method, and its application. Background Technology
[0002] Traditional polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) based solid electrolytes suffer from insufficient mechanical strength, high filler-matrix interfacial impedance, and limited dielectric properties, making it difficult to meet the electrolyte material requirements of high-energy-density batteries. In existing technologies, while single surface modification or crosslinking treatments can partially improve performance, they often lead to a decrease in ionic conductivity or increased processing difficulty. For example, while conventional silane coupling agent-modified fillers can enhance interfacial bonding, they cannot simultaneously improve the dielectric constant; and while peroxide crosslinking can enhance mechanical properties, excessive crosslinking can restrict polymer chain movement and hinder lithium-ion migration. Furthermore, in homogeneous composite structures, the uniform dispersion of fillers throughout the electrolyte prevents the formation of a high-concentration filler barrier on the surface to suppress dendrite growth, while excessive filler in the internal regions hinders the continuity of ion channels.
[0003] For example, prior art CN114566699B discloses a method for preparing a fluorinated composite lithium-ion solid electrolyte, including the following steps: Step 1, adding a silane coupling agent, a fluorinated monomer, and an initiator to an organic solvent, heating to obtain a reaction product, removing the solvent from the reaction product to obtain a fluorinated polymer; Step 2, dissolving the fluorinated polymer in an organic solvent, then adding a lithium salt to obtain a polymer system; dispersing an inorganic filler in an organic solvent and adding it to the polymer system to obtain a mixture; casting the polymer system onto a polytetrafluoroethylene plate, drying to obtain a composite electrolyte. A solid electrolyte membrane; based on the total weight of the synthesized fluorinated composite lithium-ion solid electrolyte, the content of the fluorinated monomer is 24-86% by weight, the content of the silane coupling agent is 3-56% by weight, the content of the lithium salt is 4-28% by weight, and the content of the inorganic filler is 3-16% by weight; the molar ratio of the silane coupling agent to the fluorinated monomer is 1:1-19; the silane coupling agent is 3-(methacryloyloxy)propyltrimethoxysilane; the fluorinated monomer is trifluoroethyl methacrylate, trifluoroethyl acrylate, hexafluorobutyl methacrylate, or hexafluorobutyl acrylate. However, this prior art obtains a fluorinated polymer by copolymerizing the fluorinated monomer with silane and then mixing it with lithium salt to improve ionic conductivity, but it lacks a cross-linked network design, and the mechanical properties are not effectively improved.
[0004] Existing technology CN115000499A discloses a fluoride composite solid electrolyte membrane, its preparation method, and its application. The solid electrolyte is prepared by uniformly mixing organic polymers, sodium salts, and fluorides in an organic solvent, followed by casting and hot pressing. The introduction of fluorides aims to form a stable sodium fluoride interface directly or through chemical reaction at the electrode-electrolyte interface during battery charging and discharging. This not only improves the ion transport rate in the solid electrolyte but also avoids undesirable side reactions at the electrolyte-sodium metal interface, enhancing the interfacial stability of the sodium anode and thus improving the electrochemical performance of the solid electrolyte. Applying this to solid-state sodium-ion batteries can give them excellent cycle and rate performance, extend their lifespan, and broaden the electrochemical window of all-solid-state sodium batteries. However, this existing technology, by introducing fluoride additives to form an interfacial layer and modifying the organic polymer, struggles to balance the synergistic optimization of dendrite protection and ion transport efficiency. Summary of the Invention
[0005] The purpose of this invention is to provide a composite solid electrolyte, its preparation method, and its application. This composite solid electrolyte significantly reduces interfacial impedance and promotes efficient lithium salt dissociation by constructing a fluorinated layer and a siloxane network in a stepwise manner. Combined with a polymer three-dimensional network structure and gradient filler design, it improves tensile strength and lithium ion transference number.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A method for preparing a composite solid electrolyte includes the following steps: S1. Inorganic filler and fluorine-containing compound are mixed and reacted under acidic conditions at 70-90℃ to obtain inorganic filler coated with fluorine layer; then fluoride ion complexing agent and silane coupling agent are added and reacted to obtain modified filler; A thermally decomposable crosslinking agent is added to the polymer, and the polymer is melt-blended to obtain a crosslinked polymer. S2. Mix the modified filler, crosslinked polymer, lithium salt and solvent evenly to obtain a slurry containing modified filler of different volume concentrations; mold the slurry to prepare a composite solid electrolyte. The composite solid electrolyte comprises a top layer, a middle layer, and an inner layer stacked sequentially; the modified filler in the top layer accounts for 30-40 vol% of the solid component by volume, the modified filler in the middle layer accounts for 15-25 vol% of the solid component by volume, and the modified filler in the inner layer accounts for 5-10 vol% of the solid component by volume. The fluorine-containing compound is one or more of ammonium fluoride, ammonium bifluoride, and sodium fluoride; The polymer is polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride.
[0007] When polyvinylidene fluoride is selected, the melt blending temperature is ≥175℃.
[0008] The solid components in the surface, middle, or inner layers of the composite solid electrolyte are cross-linked polymers and modified fillers.
[0009] This invention innovatively integrates a triple synergistic mechanism: by constructing a fluorinated layer and a siloxane network stepwise, it significantly reduces interfacial impedance by more than 30% and promotes efficient lithium salt dissociation; combined with a three-dimensional network structure formed by crosslinking polymers using a thermally decomposable crosslinking agent, it increases tensile strength to ≥8MPa while maintaining ionic conductivity ≥1×10⁻⁶. -3 S / cm (25℃); further, through the gradient design of modified fillers, a dense dendritic barrier of 30-40 vol% high dielectric filler is formed on the surface, 15-25% is retained in the middle layer, and 5-10 vol% filler is retained in the interior to maintain continuous ion channels, thereby increasing the lithium ion transference number to ≥0.6.
[0010] According to embodiments of the present invention, the present invention can be further optimized, and the optimized technical solution is as follows: In one preferred embodiment, the fluorinated layer has a thickness of 10-50 nm and a dielectric constant of not less than 45.
[0011] When the fluorinated layer thickness is too low, the fluorinated layer (LiF / Li2O composite phase) forms a dense structure due to excessively high grain boundary density, which blocks Li. + Transport issues lead to a decrease in ionic conductivity. Additionally, an insufficiently thick fluorinated layer may not completely cover surface defects in the filler, increasing the risk of dendrite puncture.
[0012] When the fluorinated layer is too thick, the high dielectric constant induces Li + Fluoride layer enrichment at the polymer / fluorinated layer interface accelerates dendrite nucleation. Simultaneously, excessively thick fluorinated layers can lead to thermal expansion mismatch between the fluorinated layer and the polymer during hot pressing and cooling, causing interfacial stress cracking and initiating microcracks.
[0013] In one preferred embodiment, the amount of the fluorinated compound added is 0.5-2 wt% of the inorganic filler.
[0014] In one preferred embodiment, the inorganic filler is perovskite ceramic powder or titanium dioxide; the perovskite ceramic powder is barium titanate or strontium titanate.
[0015] In one preferred embodiment, the inorganic filler, titanium dioxide, is in the rutile crystal form.
[0016] In one preferred embodiment, the inorganic filler has an average particle size of 1-10 μm.
[0017] In one preferred embodiment, the silane coupling agent is one or more of γ-glycidoxypropyltrimethoxysilane (KH560), γ-aminopropyltriethoxysilane (KH550), or γ-methacryloyloxypropyltrimethoxysilane (KH570).
[0018] In one preferred embodiment, the amount of the silane coupling agent added is 1-3 wt% of the inorganic filler.
[0019] Insufficient silane coupling agent addition will result in inadequate surface coverage, leading to ion transport blockage; excessive silane coupling agent addition will cause side reactions that consume crosslinking agents, and at the same time, excessive multilayer self-condensation caused by the silane coupling agent will lead to interface embrittlement. In addition, excessive silane coupling agent will also increase the viscosity of the system, making slurry processing more difficult.
[0020] In one preferred embodiment, the acidic condition is an environment with a pH of 3-6.
[0021] In one preferred embodiment, the fluoride ion complexing agent is an aliphatic hydroxy acid containing 2-4 carboxyl groups, preferably citric acid, tartaric acid, or malic acid.
[0022] In one preferred embodiment, the thermally decomposable crosslinking agent is one or more of dicumyl peroxide (DCP), benzoyl peroxide (BPO), or azobisisobutyronitrile (AIBN).
[0023] In one preferred embodiment, the amount of the thermally decomposable crosslinking agent added is 0.1-1.5 wt% of the polymer.
[0024] By adjusting the amount of crosslinking agent added (0.1-1.5wt%), the mechanical properties are enhanced while maintaining the chain segment mobility, thus ensuring ion transport efficiency.
[0025] In one preferred embodiment, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), or lithium hexafluorophosphate (LiPF6).
[0026] In one preferred embodiment, the amount of lithium salt added is 10-15 wt% of the crosslinked polymer.
[0027] In one preferred embodiment, the amount of solvent added is 60-80 wt% of the total mass of the slurry.
[0028] In one preferred embodiment, the solvent is one or more of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), tetrahydrofuran (THF), dimethylacetamide (DMAc), and acetone (ACE).
[0029] In one preferred embodiment, in step S2, the slurry is formed in one step or in a two-step composite process.
[0030] In one preferred embodiment, the two-step composite molding process of the slurry includes: first, preparing a single-layer homogeneous membrane by means of hot pressing, solution casting or 3D printing of each slurry; then stacking the single-layer homogeneous membranes according to the concentration of modified filler from low to high; and finally hot pressing at 180-200℃ and 8-12MPa for 10-15 minutes to obtain a composite solid electrolyte.
[0031] In one preferred embodiment, the hot pressing process is as follows: temperature 160-180℃, pressure 5-10MPa, time 5-10 minutes.
[0032] In one preferred embodiment, the solution casting process is as follows: the slurry is cast onto the substrate, leveled, and vacuum dried at 80-100°C for 24-48 hours.
[0033] In one preferred embodiment, the 3D printing process is as follows: the nozzle temperature is 170-190℃, the printing speed is 5-15mm / s, and the layer thickness is 50-100μm.
[0034] In one preferred embodiment, the one-step slurry forming step includes: depositing each slurry in a multi-channel 3D printing process according to the concentration of the modified filler from low to high, thereby obtaining a composite solid electrolyte in one step.
[0035] In one preferred embodiment, the multi-channel 3D printing process is as follows: using a coaxial multi-channel 3D printer, the slurry is loaded into the hoppers respectively, and three layers of slurry are extruded in sequence according to the filler concentration gradient; the nozzle temperature is 180-220℃, the printing speed is 8-12mm / s, the layer thickness is 50-200μm, and the interlayer cooling time is ≤10 seconds.
[0036] Based on the same inventive concept, the present invention also claims protection for the composite solid electrolyte prepared by the preparation method.
[0037] In one preferred embodiment, the composite solid electrolyte has an ionic conductivity ≥ 8 × 10⁻⁶. -4 S / cm (25℃, EIS test), tensile strength ≥8MPa (ASTM D638), electrochemical window ≥5.0V vs. Li + / Li (linear scan voltammetry, scan rate 0.5 mV / s), lithium ion transference number ≥ 0.6 (Bruce-Vincent method).
[0038] In one preferred embodiment, the thickness of the composite solid electrolyte is 50-200 μm.
[0039] Based on the same inventive concept, the present invention also claims a battery comprising the composite solid electrolyte.
[0040] In one preferred embodiment, the battery is a lithium-ion battery, a sodium-ion battery, or a lithium-sulfur battery.
[0041] Among them, lithium-ion batteries have an efficiency of 0.2 mA / cm². 2 Stable cycle duration ≥ 500 hours.
[0042] The present invention will be further explained below: This invention innovatively integrates a triple synergistic mechanism: by constructing a fluorinated layer and a siloxane network stepwise; and by combining a three-dimensional network structure formed by crosslinking polymers with a thermally decomposable crosslinking agent and a gradient filler design, the three elements of "interface modification to reduce transport resistance - crosslinking to enhance structural stability - gradient design to optimize force / electric field distribution" form a closed-loop optimization, resulting in the following core effects: (1) breaking through the contradiction of "high ionic conductivity - low mechanical strength" in traditional electrolytes; (2) solving the coupling problem of dendrite growth and interface failure in solid-state batteries; (3) achieving long-term lithium symmetric battery cycling (Example 1, lithium symmetric battery at 0.2 mA / cm 2 (Stable cycling for 600 hours at current density) provides a technological basis for high energy density batteries of 400Wh / Kg level.
[0043] This synergistic system enables the electrolyte to operate at 0.2 mA / cm². 2 It achieves stable cycling of lithium symmetric batteries for ≥500 hours at current density, extending cycle life by 40% and increasing ionic conductivity by 3 times. It is also compatible with industrial processes such as hot pressing and 3D printing, providing a reliable solution for high energy density and high safety energy storage devices.
[0044] The mechanism of this invention is explained below: Mechanism and mechanism of simultaneous construction of fluorinated layer and siloxane network The atomic-level synergistic construction of the fluorinated layer (rigid ionic conductor) and the siloxane network (flexible interfacial bridge) on the filler surface involves a three-step coupling reaction mechanism: I. Stepwise Reaction Path and Spatial Positioning (1) Embedded construction of fluorinated layer Under acidic conditions, fluorine-containing compounds decompose to release F. - By embedding itself into the perovskite lattice through an ion substitution reaction, the Li+ migration barrier is lowered. .
[0045] (2) Epitaxial growth of siloxane network After the fluorinated layer is constructed, without changing the reaction system, a silane coupling agent is directly added to trigger the following reaction under residual acidic conditions (using KH560 as an example): Hydrolysis reaction:
[0046] .
[0047] Condensation reaction: (Bonded with the fluorinated layer).
[0048] (Network self-assembly).
[0049] II. Interfacial Chemical Bonding Mechanism (1) Covalent bonding The Si-O bonds in the siloxane network form Si-O-Ti bonds with the Ti atoms on the surface of the fluorinated layer; the residual F- forms Si-F bonds with Si-OH.
[0050] (2) Ion-dipole interaction The highly electronegative F- in the fluorinated layer is electrostatically attracted to the epoxy groups of the silane.
[0051] The fluorinated layer forms the inner rigid framework, while the siloxane network forms the outer flexible coating layer.
[0052] III. Synergistic Enhancement Reactions Constructed Simultaneously Fluoride layer reduces Li + The migration barrier is eliminated by the siloxane network, which eliminates interfacial voids and synergistically reduces the total interfacial impedance. The fluorinated layer increases the filler modulus, and the siloxane network forms an elastic buffer layer, which synergistically improves mechanical strength. The fluorinated layer promotes lithium salt dissociation, and the siloxane network provides continuous transition sites, which synergistically improves ion transport efficiency.
[0053] 2. Formation mechanism of three-dimensional crosslinked network in polymers by thermally decomposable crosslinking agents (1) Free radical initiation and chain reaction Thermally decomposable crosslinking agents undergo homolytic decomposition at a certain temperature, generating highly reactive free radicals (taking DCP as an example): .
[0054] Cryophenyloxy radical (CP) It further decomposes into acetone and methyl free radicals. ) (2) Polymer chain activation The resulting free radicals attack the polymer molecular chains (such as PVDF-HFP): Free radicals (R·) take hydrogen atoms from methylene (-CH2-) or tertiary carbon sites in polymer molecular chains such as PVDF-HFP chains (the strong electronegativity of fluorine atoms reduces the energy of adjacent CH bonds, making them more susceptible to attack), forming macromolecular free radicals (P·). .
[0055] Adjacent macromolecular free radicals form C-C covalent crosslinks through coupling reactions. This process continues within the polymer melt, ultimately constructing a three-dimensional network structure that permeates the matrix (e.g., ...). Figure 2 ).
[0056] .
[0057] 3. Synergistic mechanism of interface modification, cross-linking enhancement, and gradient structure (1) Functional complementarity and synergy Filler interface modification: reduce interfacial impedance and provide low-resistance ion channels for gradient structures; Polymer crosslinking reinforcement: improves mechanical strength and supports the gradient structure against dendrite penetration; Gradient structure design: Optimize ion / stress distribution and amplify the effectiveness of interface modification and crosslinking.
[0058] (2) Cross-scale structural coupling mechanism Nanoscale: Interface-Matrix Molecular Interlocking The epoxy groups of the silane coupling agent form a "dipole-dipole" interaction with the CF bonds of the crosslinked PVDF-HFP, which reduces the filler / matrix interfacial energy; the free radicals in the crosslinked network capture residual chloride ions, preventing them from corroding lithium salts (such as LiPF6) and improving interfacial stability.
[0059] Micrometer Scale: Gradient-Crosslinking Stress Synergy The surface layer (high filler) bears most of the external stress and then disperses it to the interior through a cross-linked network; the interior layer (low filler) absorbs stress by a flexible matrix and inhibits the propagation of microcracks.
[0060] Macroscopic Scale: Electrochemical-Mechanical Performance Balance The gradient surface layer with a high dielectric barrier (fluoride + high filler) enhances the critical dendrite penetration pressure; the cross-linked network maintains the toughness of the matrix, enabling high ionic conductivity and high mechanical strength to be achieved simultaneously.
[0061] (3) Dynamic coordination The strong polarization field of the fluorinated layer reduces the Li + Deionization of anions (TFSI) - The energy barrier of (etc.) promotes the accelerated dissociation of lithium salts; Siloxane networks provide low-barrier transition sites, enhancing interfacial transitions; The low-filler zone inside the gradient forms a continuous flow channel, which increases the ion transport number and enhances the bulk transport of lithium ions.
[0062] Compared with the prior art, the beneficial effects of the present invention are: This invention achieves a comprehensive improvement in the performance of composite solid electrolytes through the synergistic effect of interface modification, crosslinking enhancement, and gradient structure design. Specifically, this is reflected in the following aspects: 1. Synergistic optimization of interface and electrochemical performance By simultaneously constructing the fluorinated layer and the siloxane network, the filler-matrix interfacial impedance is significantly reduced by more than 30%, while promoting the efficient dissociation of lithium salt and increasing the electrolyte ionic conductivity to ≥8×10⁻⁶. -4 S / cm (25℃).
[0063] 2. Enhanced mechanical strength and thermal stability By employing thermally decomposable crosslinking agents such as dicumyl peroxide (DCP) and benzoyl peroxide (BPO), a three-dimensional crosslinked network is formed in the fluoropolymer matrix, enabling the material to achieve a tensile strength of ≥8 MPa (ASTM D638 standard test) and raising the thermal decomposition temperature to over 380℃. This enhances mechanical properties while maintaining chain segment mobility, ensuring efficient ion transport.
[0064] 3. Gradient structure inhibits dendrite growth Through a gradient composite structure design, a dense barrier of 20-30 vol% high-dielectric filler is introduced into the electrolyte surface region to effectively suppress lithium dendrite penetration; the internal region maintains a filler content of 5-15 vol% to retain continuous ion channels. Combined with lithium salt concentration optimization, the polymer crystallinity is reduced to below 30%, and the lithium ion transference number is increased to ≥0.6, achieving a synergistic effect of ion transport and dendrite protection.
[0065] 4. Process adaptability and application expandability The electrolyte is compatible with various fabrication processes such as hot pressing and 3D printing, and is suitable for solid-state lithium-ion batteries, solid-state sodium-ion batteries, and lithium-sulfur batteries. By controlling the fluoride layer thickness (10-50 nm), crosslinking density (gel fraction 60-90%), and lithium salt concentration (5-20 wt%), the electrochemical performance (electrochemical window ≥ 5.0 V vs. Li+ / Li) and mechanical properties (elongation at break ≥ 150%) can be customized, achieving a lithium symmetric battery performance of 0.2 mA / cm². 2 Stable cycling at current density for ≥500 hours provides a reliable technical solution for high-safety energy storage devices. Attached Figure Description
[0066] Figure 1 This is a schematic diagram of the principle and structure of inorganic filler modification.
[0067] Figure 2 This is a schematic diagram of polymer crosslinking.
[0068] Figure 3 It is a high-power microscope showing the cross-section of a gradient electrolyte membrane.
[0069] Figure 4 This is a graph showing the ionic conductivity of Example 1.
[0070] Figure 5 This is a graph showing the ionic conductivity of Example 2.
[0071] Figure 6 This is the ionic conductivity curve for Example 3.
[0072] Figure 7 This is the ionic conductivity curve for Example 4.
[0073] Figure 8 This is a graph showing the ionic conductivity of Comparative Example 1.
[0074] Figure 9 The graph shows the ionic conductivity of Comparative Example 2.
[0075] Figure 10 This is a graph showing the ionic conductivity of Comparative Example 3.
[0076] Figure 11 This is a graph showing the ionic conductivity of Comparative Example 4.
[0077] Figure 12 This is a voltage-time curve of a lithium symmetric battery in Example 1.
[0078] Figure 13 This is a SEM image of the porous electrolyte membrane in Example 3. Detailed Implementation
[0079] This invention is not limited to the specific embodiments listed below. Those skilled in the art can implement this invention using various other specific embodiments based on the content disclosed herein. Any modifications or alterations made to the design structure and concept of this invention fall within the protection scope of this invention. It should be noted that, unless otherwise specified, the embodiments and features described in this invention can be combined with each other.
[0080] In this invention, the ionic conductivity of the electrolyte membrane was tested at 25±5℃ using EIS. Tensile strength was obtained using ASTM D638. The electrochemical window was tested using linear sweep voltammetry at a scan rate of 0.5 mV / s, and the lithium-ion transference number was tested using the Bruce-Vincent method.
[0081] Example 1
[0082] A method for preparing a composite solid electrolyte based on modified barium titanate filler, the specific implementation steps of which are as follows: 1. Surface modification of fillers 10 g of barium titanate (BaTiO3, average particle size 1 μm) was dispersed in 200 mL of ethanol / water mixture (volume ratio 8:2) and sonicated for 30 minutes to form a homogeneous suspension. First, 0.15 g of ammonium fluoride (1.5% of the filler mass) was added, and the pH of the system was adjusted to 4.5 with dilute hydrochloric acid. The mixture was stirred at 80 °C for 4 hours to allow fluoride ions to replace oxygen ions on the barium titanate surface, forming a fluorinated layer. Subsequently, maintaining the same pH and temperature, 0.2 g of silane coupling agent KH560 (2% of the filler mass) and 0.03 g of citric acid (0.3% of the filler mass) were added, and stirring continued for 2 hours to complete the hydrolysis and condensation reaction of KH560. Simultaneously, citric acid complexed residual fluoride ions to suppress side reactions. After the reaction, the modified barium titanate (BT@F-KH560) was obtained by centrifugation (8000 rpm, 10 minutes), washing three times with ethanol, and vacuum drying at 80 °C for 12 hours. Schematic diagrams of the principle and structure of barium titanate modification are as follows: Figure 1 As shown.
[0083] 2. Polymer matrix crosslinking 10g of PVDF-HFP (HFP content 12wt%) was dry-mixed with 0.05g of dicumyl peroxide (DCP, accounting for 0.5% of PVDF-HFP by mass) until homogeneous. The mixture was then melt-blended using a twin-screw extruder at 180-200℃ and 50rpm for 5 minutes. The free radicals generated by the decomposition of DCP at high temperature initiated cross-linking of the CF bonds between the PVDF-HFP molecular chains, forming a three-dimensional network structure of the cross-linked polymer. A schematic diagram of the cross-linked polymer is shown below. Figure 2 As shown.
[0084] 3. Composite electrolyte membrane molding The cross-linked polymer, surface-modified barium titanate (BT@F-KH560), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, 15% of the cross-linked polymer by mass) were ball-milled in N-methylpyrrolidone (75 wt% of the total slurry mass) for 4 hours (300 rpm) to obtain the surface slurry. In the surface slurry, the BT@F-KH560 filler accounted for 30% of the volume of the solid component (cross-linked polymer + surface-modified barium titanate), and the cross-linked polymer accounted for 70% of the volume.
[0085] The crosslinked polymer, surface-modified barium titanate (BT@F-KH560), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, accounting for 15% of the crosslinked polymer by mass) were ball-milled in N-methylpyrrolidone solvent for 4 hours (300 rpm) to obtain the intermediate layer slurry. In the intermediate layer slurry, the BT@F-KH560 filler accounted for 15% of the solid component by volume, and the crosslinked polymer accounted for 85% by volume.
[0086] The crosslinked polymer, surface-modified barium titanate (BT@F-KH560), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, accounting for 15% of the crosslinked polymer by mass) were ball-milled in N-methylpyrrolidone solvent for 4 hours (300 rpm) to obtain the bottom layer slurry. In the bottom layer slurry, the BT@F-KH560 filler accounted for 5% of the solid component by volume, and the crosslinked polymer accounted for 95% by volume.
[0087] Three layers of slurry were sequentially stacked and coated, then hot-pressed at 185℃ and 12MPa for 12 minutes to obtain a three-layer gradient electrolyte membrane with a total thickness of 150μm. The cross-sectional gradient distribution was characterized using a high-power microscope (Keyence VHX-X1). Figure 3 As shown.
[0088] Scanning electron microscopy (SEM) was performed on the three-layer gradient electrolyte membrane, such as... Figure 4 As shown in the figure. The results show that the surface layer is dense and non-porous, with an ionic conductivity of 9.43 × 10⁻⁶ at 25 °C. -4 S / cm ( Figure 4 The lithium-ion transference number (Bruce-Vincent method) is 0.65.
[0089] A lithium-ion symmetric battery was assembled using a three-layer gradient electrolyte membrane, and its performance was tested. The process was as follows: A 16mm diameter three-layer gradient electrolyte membrane was sandwiched between two 15mm diameter, 200μm thick lithium metal sheets, and then encapsulated in a CR2032 battery case under a pressure of 10MPa to obtain a lithium-ion symmetric battery. The lithium-ion symmetric battery was tested at 0.2mA / cm². 2 The cycle performance of the lithium symmetric battery at 0.2 mA / cm² was tested, and the results showed that the battery performed well at this temperature. 2 No dendrite formation was observed after 600 hours of stable cycling. Figure 12 ).
[0090] Mechanical property analysis of the three-layer gradient structure electrolyte membrane showed that the tensile strength reached 9.5 MPa and the elongation at break was 180%.
[0091] Example 2
[0092] Based on Example 1, barium titanate was replaced with strontium titanate (SrTiO3, average particle size 0.8 μm), and the addition amounts of NH4F and KH560 were 1% and 3% of the filler mass, respectively. The reaction was carried out at pH 5.0 and 75℃ for 7 hours to obtain SrTiO3@F-KH560 modified filler.
[0093] The gradient electrolyte membrane was prepared using the same three-layer hot-pressing process as in Example 1, i.e., hot-pressed at 185°C and 12 MPa for 12 minutes. The properties of the prepared gradient electrolyte membrane are as follows: Regarding structural characteristics, scanning electron microscopy (SEM) images show that its surface exhibits a dense, non-porous structure. Electrochemical performance tests indicate that the ionic conductivity measured by electrochemical impedance spectroscopy (EIS) at 25℃ is 8.84 × 10⁻⁶. -4 S / cm ( Figure 5 The lithium-ion transport number, determined using the Bruce-Vincent method, was 0.65. Mechanical property tests showed a tensile strength of 12.8 MPa and an elongation at break of 180%, as measured according to ASTM D638. The lithium-ion symmetric battery operates at 0.2 mA / cm². 2 No dendrite formation was observed after 500 hours of cycling at the current density.
[0094] Example 3
[0095] Based on Example 1, DCP was replaced with benzoyl peroxide (BPO, added at 0.8 wt% of the polymer), and PVDF-HFP crosslinking was completed at a melting temperature of 170°C using a twin-screw extruder (temperature gradient 165-185°C, speed 45 rpm).
[0096] Everything else is the same as in Example 1.
[0097] Crosslinked PVDF-HFP, modified filler (BT@F-KH560), and LiFSI (based on 15% of the mass of crosslinked PVDF-HFP) were dissolved in DMF solvent (75wt% of the total slurry mass). After thorough mixing, the three slurries were deposited layer by layer using a 3D printing device (using a coaxial multi-channel 3D printer, where the slurries were loaded into the hoppers and extruded in sequence according to the filler concentration gradient; three nozzles were used to print the three slurries respectively, with a nozzle temperature of 190℃ and a printing speed of 10mm / s). After vacuum drying at 80℃ for 48 hours, a porous electrolyte membrane was obtained. The porous electrolyte membrane was analyzed by SEM, and the results are as follows: Figure 13 As shown in the figure. Tests indicate that the membrane porosity is 35% and the ionic conductivity reaches 8.60 × 10⁻⁶. -4 S / cm ( Figure 6 ).
[0098] Example 4
[0099] Based on Example 1, lithium salt LiTFSI was replaced with sodium salt NaTFSI (10 wt% of the crosslinked polymer mass), and La was used as the filler. 3+ Barium titanate doped (BaTiO3:La, chemical formula Ba) 0.95 La 0.05 TiO3, the preparation method and structural characterization refer to the existing technology: GUO S, TAN S, MA J, etc. A dielectric electrolyte composite with high lithium-ion conductivity for high-voltage solid-state lithium metalbatteries [J]. Energy & Environmental Science, 2024, 17: 3797-3806 and the existing technology SHI P, MA J, LIU M, etc. Dissociation mechanism of lithium salt by BaTiO3 with spontaneous polarization [J]. Nature Nanotechnology, 2023, 18: 602-610), and the modification and composite film preparation are carried out according to the process of Example 1.
[0100] The performance test results of the composite membrane are as follows: The resulting electrolyte membrane (16 mm in diameter) was sandwiched between a sodium metal anode (15 mm in diameter and 200 μm in thickness) and a Na3V2(PO4)3 cathode. The cathode consisted of 85 wt% Na3V2(PO4)3, 10 wt% Super P conductive agent, and 5 wt% PVDF binder, with an active material surface loading of 8 mg / cm³. 2 The battery was encapsulated in a CR2032 battery case under 10 MPa pressure and operated entirely in an argon glove box (water oxygen value < 0.1 ppm) to obtain a Na|electrolyte|Na3V2(PO4)3 battery (structure referenced from existing technology: SHANGJ, MA Y, FAN HJ S. Preparation of Na3V2(PO4)3 sodium-ion battery cathode material [J]. Asia-Pacific Journal of Chemical Engineering, 2023, 18(3):e2882). The sodium ion conductivity at 25℃ was measured to be 9.66 × 10⁻⁶. -4 S / cm ( Figure 7The Na|electrolyte|Na3V2(PO4)3 battery, tested using the Xinwei BTS-5V10mA battery testing system, maintained a capacity retention of over 90% after 200 cycles at 0.5C rate, with a coulombic efficiency consistently above 99.2%.
[0101] Comparative Example 1
[0102] Unmodified filler and uncrosslinked PVDF-HFP
[0103] Based on Example 1, using unmodified BaTiO3 and uncrosslinked PVDF-HFP, with the remaining processes the same as in Example 1, the prepared electrolyte had an ionic conductivity of only 2.32 × 10⁻⁶. -4 S / cm ( Figure 8 The tensile strength drops sharply to 1.7 MPa, and the lithium symmetric battery has a strength of 0.2 mA / cm. 2 Dendrites appeared after 200 hours of the next cycle.
[0104] Comparative Example 2
[0105] Based on Example 1, unmodified BaTiO3 was used, and the remaining processes were the same as in Example 1. Scanning electron microscopy analysis of the prepared electrolyte showed relatively obvious phase separation at the filler-matrix interface. The ionic conductivity at 25℃ was 4.37 × 10⁻⁶. -4 S / cm ( Figure 9 The lithium-ion transport number, measured by the Bruce-Vincent method, was 0.31. The tensile strength decreased to 5.2 MPa. The lithium-ion symmetric cell operated at 0.2 mA / cm². 2 Dendrite penetration occurred after 73 hours of the next cycle.
[0106] Comparative Example 3
[0107] Based on Example 1, uncrosslinked PVDF-HFP was used, with the remaining processes identical to Example 1. Differential scanning calorimetry (DSC) showed a significantly reduced glass transition temperature (Tg = -42℃), and a thermal shrinkage rate of 15.8% at 80℃. Electrochemical impedance spectroscopy (EIS) analysis showed an ionic conductivity of 7.05 × 10⁻⁶ at 25℃. -4 S / cm ( Figure 10 The lithium-ion transport number, measured by the Bruce-Vincent method, was 0.38. The tensile strength decreased to 5.2 MPa. The lithium-ion symmetric cell operated at 0.2 mA / cm². 2 Dendrite penetration occurred after 48 hours of cycling. Significant deformation of the film occurred after being placed at 60°C for 24 hours.
[0108] Comparative Example 4
[0109] Based on Example 1, instead of using a gradient packing design, a single-concentration packing design is used, and the specific operation is as follows:
[0110] 8g of crosslinked polymer, 2g of surface-modified barium titanate (BT@F-KH560), and 1.2g of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI, accounting for 15% of the crosslinked polymer mass) were ball-milled in N-methylpyrrolidone solvent for 4 hours (300 rpm). After vacuum degassing, the mixture was hot-pressed at 190°C and 10MPa for 10 minutes to obtain a homogeneous electrolyte membrane with a thickness of 100μm. Other steps were the same as in Example 1.
[0111] The properties of the prepared electrolyte are as follows: Electrochemical impedance spectroscopy (EIS) analysis showed an ionic conductivity of 1.30 × 10⁻⁶ at 25 °C. -3 S / cm ( Figure 11 The dielectric constant (1kHz) test showed ε'=48; the tensile strength test showed 6.5MPa; and the elongation at break was 135%. The test was conducted on a lithium-ion symmetric battery at 0.2mA / cm². 2 Cycling performance at current density showed that dendrite penetration occurred after 500 hours of stable cycling in the lithium symmetric battery.
[0112] Comparative Example 5
[0113] Based on Example 1, instead of using fluoride-modified fillers, only silane coupling agents were used for modification, resulting in inorganic fillers coated solely with coupling agents. Everything else remained the same as in Example 1.
[0114] The performance characterization of the obtained electrolyte membrane shows that: In terms of microstructure, scanning electron microscopy (SEM) showed local voids at the interface between the filler and the polymer matrix, and energy dispersive spectroscopy (EDS) confirmed the absence of fluorine at the interface.
[0115] In the electrochemical performance test, the ionic conductivity at 25℃ was 7.85 × 10⁻⁶. -4 S / cm (significantly lower than in Example 1), and lithium-ion transference number reduced to 0.35.
[0116] The mechanical properties were as follows: tensile strength of 9.2 MPa and elongation at break of 125%, which were 29.2% and 30.6% lower than those of Example 1, respectively.
[0117] In battery cycle testing, the lithium symmetric battery achieved a speed of 0.2 mA / cm². 2 Voltage fluctuations occurred after 214 hours of cycling at the current density.
[0118] Comparative Example 6
[0119] Based on Example 1, instead of using silane coupling agents to modify the filler, only fluoride modification was used to obtain an inorganic filler with sole fluoride coating. Everything else is the same as in Example 1.
[0120] Performance test results show that: The agglomeration of filler particles was observed in the microstructure using a high-magnification microscope, and X-ray photoelectron spectroscopy (XPS) confirmed the disappearance of the characteristic peak of silicon on the surface and the local enrichment of fluorine.
[0121] In terms of electrochemical performance, the ionic conductivity at 25℃ is 6.92 × 10⁻⁶. -4 S / cm (significantly lower than in Example 1), lithium-ion transference number of 0.37, and electrochemical window narrowed to 4.5V (vs. Li). + / Li).
[0122] Mechanical property tests showed a tensile strength of 10.8 MPa and an elongation at break of 142%.
[0123] The battery performance is comparable to that of a lithium-ion symmetric battery at 0.2 mA / cm². 2 Voltage oscillations occurred after 158 hours of cycling, and upon disassembly, delamination of the electrode-electrolyte interface was observed.
[0124] Comparative Example 7
[0125] Based on Example 1, the filler surface modification process was adjusted: silane coupling agent KH560 and ammonium fluoride (NH4F) were pre-mixed and reacted in ethanol solvent to obtain a fluorinated polymer solution, and then the barium titanate filler was coated in one step. The remaining process parameters were the same as in Example 1.
[0126] Performance characterization shows: In the microstructure analysis, scanning electron microscopy (SEM) showed that the coating thickness on the filler surface was uneven, and X-ray photoelectron spectroscopy (XPS) detected the characteristic peak of Si-F bond (687.2 eV), while the intensity of the filler characteristic peak decreased.
[0127] The electrochemical performance showed that the ionic conductivity decreased to 6.24 × 10⁻⁶ at 25 °C. -4 S / cm (lower than in Example 1), lithium-ion transference number is 0.33.
[0128] In the thermomechanical property test, the tensile strength was 7.5 MPa (a decrease of 42.3% compared to Example 1), and the heat shrinkage rate at 80°C reached 8.7%.
[0129] Battery cycle tests show that lithium symmetric batteries perform well at 0.2 mA / cm². 2 An internal short circuit occurred after 110 hours of cycling at the current density.
[0130] Comparative Example 8
[0131] Based on Example 1, trifluoroethyl methacrylate was used as the fluorinated compound to replace ammonium fluoride, and the rest was the same as in Example 1.
[0132] Performance test results show that: In the microstructure characterization, transmission electron microscopy (TEM) showed that an amorphous organic coating layer with a thickness of about 25 nm was formed on the surface of the filler.
[0133] In terms of electrochemical performance, the ionic conductivity at 25℃ is 6.21 × 10⁻⁶. -4 S / cm (significantly lower than in Example 1), and lithium-ion transference number decreased to 0.31.
[0134] Mechanical property tests showed a tensile strength of 8.3 MPa and an elongation at break that decreased to 118%.
[0135] The battery performance is comparable to that of a lithium-ion symmetric battery at 0.2 mA / cm². 2 Dendrite penetration occurred after 85 hours of the next cycle.
[0136] Comparative Example 9
[0137] Based on Example 1, uncrosslinked PVDF-HFP was used, and PVDF-HFP was modified with ammonium fluoride. The specific operation is as follows:
[0138] Weigh 10g of PVDF-HFP (HFP content 12wt%), weigh 10wt% of the polymer ammonium fluoride, dissolve in 10 mL of acetonitrile, and stir on a stirring table at 25 ℃ for 12 h to form a homogeneous solution. Other steps are the same as in Example 1.
[0139] Performance test results show: In the microstructure characterization, scanning electron microscopy (SEM) observed that sodium fluoride formed 1-5 μm aggregates in the polymer matrix, and energy dispersive spectroscopy confirmed that fluorine was locally enriched.
[0140] In terms of electrochemical performance, the ionic conductivity at 25℃ is 7.02 × 10⁻⁶. -4 S / cm (significantly lower than in Example 1), and the lithium-ion transference number decreased to 0.28.
[0141] Mechanical property tests showed that the tensile strength decreased to 7.8 MPa, and the heat shrinkage rate at 80℃ reached 17.3%.
[0142] The battery performance is comparable to that of a lithium-ion symmetric battery at 0.2 mA / cm². 2 A short circuit occurred after 87 hours of cycling at the current density.
[0143] Comparative Example 10
[0144] The composite solid electrolyte was prepared according to the method described in Example 1 of CN114566699B: 3-(methacryloyloxy)propyltrimethoxysilane and trifluoroethyl methacrylate were dissolved in acetonitrile at a molar ratio of 1:5, and 0.5wt% azobisisobutyronitrile was added. The mixture was reacted at 80°C for 12 hours to obtain a fluoropolymer. The fluoropolymer, 10wt% lithium bis(trifluoromethanesulfonyl)imide and 15vol% barium titanate were mixed and cast into a film with a thickness of 100μm.
[0145] Mechanical property testing showed that the electrolyte had a tensile strength of 2.8 MPa (ASTM D638) and an elongation at break of 45%, which is suitable for lithium-ion symmetric batteries at 0.1 mA / cm². 2 Voltage fluctuations (>100mV) appeared after 150 hours of cycling at the current density, indicating dendrite penetration. Its mechanical properties are significantly worse than those of Example 1.
[0146] Compared with Comparative Example 10, the composite electrolyte membrane prepared in Example 1 of the present invention has a tensile strength increased by 239%, a cycle life extended by 300%, and a dendrite critical puncture pressure > 8.0 MPa (microprobe indentation method).
[0147] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of this invention are still within the scope of protection of this invention.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that, Includes the following steps: S1. Inorganic filler and fluorine-containing compound are mixed and reacted under acidic conditions at 70-90℃ to obtain inorganic filler coated with fluorine layer; then fluoride ion complexing agent and silane coupling agent are added and reacted to obtain modified filler; A thermally decomposable crosslinking agent is added to the polymer, and the polymer is melt-blended to obtain a crosslinked polymer. S2. Mix the above modified filler, crosslinked polymer, lithium salt and solvent evenly to obtain a variety of slurries containing different volume concentrations of modified filler; mold the various slurries to prepare a composite solid electrolyte; The composite solid electrolyte comprises a top layer, a middle layer, and an inner layer stacked sequentially; the modified filler in the top layer accounts for 30-40 vol% of the solid component by volume, the modified filler in the middle layer accounts for 15-25 vol% of the solid component by volume, and the modified filler in the inner layer accounts for 5-10 vol% of the solid component by volume. The fluorine-containing compound is one or more of ammonium fluoride, ammonium bifluoride, and sodium fluoride; The polymer is polyvinylidene fluoride-hexafluoropropylene copolymer or polyvinylidene fluoride.
2. The preparation method according to claim 1, characterized in that, The amount of the fluorinated compound added is 0.5-2 wt% of the inorganic filler.
3. The preparation method according to claim 1, characterized in that, The inorganic filler is perovskite ceramic powder or titanium dioxide, and the perovskite ceramic powder is barium titanate or strontium titanate.
4. The preparation method according to claim 1, characterized in that, The silane coupling agent is one or more of γ-glycidoxypropyltrimethoxysilane, γ-aminopropyltriethoxysilane, or γ-methacryloyloxypropyltrimethoxysilane; the amount of the silane coupling agent added is 1-3 wt% of the inorganic filler.
5. The preparation method according to claim 1, characterized in that, The acidic conditions are an environment with a pH of 3-6; the fluoride ion complexing agent is citric acid.
6. The preparation method according to claim 1, characterized in that, The thermally decomposable crosslinking agent is one or more of dicumyl peroxide, benzoyl peroxide, or azobisisobutyronitrile; the amount of the thermally decomposable crosslinking agent added is 0.1-1.5 wt% of the polymer.
7. The preparation method according to claim 1, characterized in that, In the slurry, the amount of lithium salt added is 10-15 wt% of the crosslinked polymer; and / or, the lithium salt is one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, and lithium hexafluorophosphate.
8. The composite solid electrolyte prepared by the preparation method according to any one of claims 1-7.
9. The composite solid electrolyte according to claim 8, characterized in that, The ionic conductivity of the composite solid electrolyte is ≥8×10⁻⁶. -4 S / cm, tensile strength ≥8MPa, electrochemical window ≥5.0V, lithium-ion transference number ≥0.
6.
10. A battery, characterized in that, The battery includes the composite solid electrolyte as described in claim 8 or 9.
Citation Information
Patent Citations
Fluorine-containing composite lithium ion solid electrolyte and preparation method thereof
CN114566699B
Fluoride composite solid electrolyte membrane and preparation method thereof, and solid sodium battery using fluoride composite solid electrolyte membrane
CN115000499A
Barium titanate modified polymer solid electrolyte preparation method and application thereof
CN109671975A
Fluorinated two-dimensional inorganic nanofiller reinforced PEO-based solid polymer electrolyte, and preparation method and application thereof
CN117438661A
Hydrophobic modified lithium aluminum titanium phosphate solid electrolyte, preparation method thereof and lithium ion battery
CN120015906A
Cited By
Fluorine ion solid polymer electrolyte and preparation method and application thereof
CN121507131A
Electrolyte film, preparation method thereof and lithium battery
CN122338226A
A lithium fluoride solid-state electrolyte, a preparation method and application thereof
CN122393405A